Representação de mulheres moçambicanas na obra de Paulina Chiziane Niketche: uma história de poligamia - Francisco, Renata Maria Teresa dos Santos (2019)
This work intends to problematize the female representations in Mozambique since the literary production of Paulina Chiziane. With the book The First Wife: A Tale of Polygamy as the main source of this research, we will look into the social roles of Mozambican women coming from diverse peoples, age groups and social classes depicted in this romance. We will highlight the subversion tactics carried out by such women that has allowed them to deconstruct the oppression to which they have been subjected to. We take on a methodological procedure which understands literature as a language capable of reinventing and reinterpreting the reality by its own means and, in dialogue with History, is able to inquire into the livelihood, knowledge and memory of these women. Paulina Chiziane has created in her work an unusual view over the female universe in contraposition to the male one in the Mozambican post independence context, what allows us to gain an insight into the livelihood as well as the affectivities within this Society